O impacto da estrutura de propriedade e controle no desempenho e governança corporativa das corporations listadas na B3 - Meneghel, Marcia Ferraz (2022)
This study aimed to analyze the effects of the dispersed ownership and control structure on the performance and corporate governance of companies listed on the Brazilian stock exchange (B)³, which fall within the parameters of corporation proposed by the research and defined by the literature. Additionally, to examine whether in the Brazilian listed companies that became corporations during the period of analysis, there was a change in the performance and in the corporate governance structure. The ownership and control structure has been shown to be one of the factors that raise the governance levels of Brazilian companies, accentuating possible agency problems and making it easier to maximize performance. Although companies in emerging economies are characterized by a concentrated ownership structure, in Brazil, the presence of companies listed on the Stock Exchange characterized as corporations, whose ownership and control structure is formed without the presence of a defined controller and with the dispersion of shares, although incipient, shows signs of growth. In this context, knowledge of the influence of an important component of corporate governance on performance and on other attributes that are part of the governance structure of companies is provided to the literature. To this end, secondary data collected directly from B³ and Economática® were used, covering the period from 2017 to 2021. The interest group that represents the dispersion of ownership and control was selected through the metric proposed by the research and another already consolidated in the literature. The analysis was carried out using descriptive statistics, test of difference between means, correlation matrix and panel data regression. Through the results, the evidence does not point to relevant impacts of the dispersed ownership and control structure on the corporate governance index and on performance. Likewise, in companies that became corporations during the analysis period, there was no change in performance and in the corporate governance structure. It is observed that the shareholding dispersion is not shown as a determining factor of the existing attributes in the corporate governance structure and of the financial and market performance, indicating that the perspective of higher levels of performance, do not establish themselves in a scenario of shareholding dispersion for the companies that make up the sample. However, the number of institutional investors was positively related to financial performance, which demonstrates the need to strengthen institutional ownership in order to stimulate the financial performance of companies. This research empirically contributes to the literature on ownership and control structure from the perspective of shareholding dispersion in an emerging market such as Brazil, in addition to providing insights to the various users of market information.